Characterization and in vivo study of decellularized aortic scaffolds using closed sonication system - Hazwani, Aqilah; Sha'ban, Munirah; Azhim, Azran (Taylor & Francis, 2019)
Extracellular matrix (ECM) based bioscaffolds prepared by decellularization has increasingly emerged in tissue engineering application because it has structural, biochemical, and biomechanical cues that have dramatic effects upon cell behaviors. Therefore, we developed a closed sonication decellularization system to prepare ideal bioscaffolds with minimal adverse effects on the ECM. The decellularization was achieved at 170 kHz of ultrasound frequency in 0.1% and 2% Sodium Dodecyl Sulphate (SDS) solution for 10 hours. The immersion treatment as control was performed to compare the decellularization efficiency with our system. Cell removal and ECM structure were determined by histological staining and biochemical assay. Biomechanical properties were investigated by the indentation testing to test the stiffness, a residual force and compression of bioscaffolds. Additionally, in vivo implantation was performed in rat to investigate host tissue response. Compared to native tissues, histological staining and biochemical assay confirm the absence of cellularity with preservation of ECM structure. Moreover, sonication treatment has not affected the stiffness [N/mm] and a residual force [N] of the aortic scaffolds except for compression [%] which 2% SDS significantly decreased compared to native tissues showing higher SDS has a detrimental effect on ECM structure. Finally, minimal inflammatory response was observed after 1 and 5 weeks of implantation. This study reported that the novelty of our developed closed sonication system to prepare ideal bioscaffolds for tissue engineering applications.